2021
DOI: 10.3390/ijerph18105166
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Review on COVID-19, Work-Related Aspects, and Age Differences

Abstract: The COVID-19 pandemic significantly impacted the labor market and multiple aspects of work and workers’ life. The present rapid review analyzes this impact considering the effects that COVID-19 pandemic had on employment and work-related aspects across different age groups. A comprehensive literature search was performed on scientific contributions published between 2019 and March 2021, resulting in 36 papers pertinent to the scope of this review. Findings were grouped according to different topics, all linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 67 publications
1
39
1
2
Order By: Relevance
“…The impact of the measures is reflected by the Gross Domestic Product (GDP) decrease of about 4.7% points (Italian Statistical Agency 30-4-2020) with respect to the previous quarter, and by 4.8% over the same quarter of the previous year: a data threatening an upcoming devastating economic recession. The COVID-19 pandemic was definitely an event that impacted work and the lives and well-being of workers (Bellotti et al, 2021;Canet-Juric et al, 2020;Mo et al, 2020).…”
Section: Workers During the Covid-19 Outbreakmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of the measures is reflected by the Gross Domestic Product (GDP) decrease of about 4.7% points (Italian Statistical Agency 30-4-2020) with respect to the previous quarter, and by 4.8% over the same quarter of the previous year: a data threatening an upcoming devastating economic recession. The COVID-19 pandemic was definitely an event that impacted work and the lives and well-being of workers (Bellotti et al, 2021;Canet-Juric et al, 2020;Mo et al, 2020).…”
Section: Workers During the Covid-19 Outbreakmentioning
confidence: 99%
“…The COVID-19 outbreak is an unprecedented event in recent times, with a tremendous negative threat to inviduals' adjustment (e.g., Alessandri et al, 2021;Bellotti et al, 2021;Canet-Juric et al, 2020), public health as well as to the economic system. For example, in the United States alone, the estimated economic damage to the labour market caused by the crisis is greater than that of the Great Recession or the 2008 crisis (Coibion et al, 2020).…”
Section: Understanding the Determinants Of Well-being In Times Of Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental changes in working conditions, along with other pandemic-related impacts on private life, constituted an unusual, long-lasting stressor for employees. Relatively older employees may be particularly vulnerable, as they face an increased health risk if they catch the virus and may feel less technologically competent [4]. Moreover, a recent rapid review found that older workers perceived remote work more negatively and reported more communication breakdowns and tensions between generations, which was likely exacerbated by stereotypes against older workers that were perpetrated by organizations and governments [4].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the COVID-19 pandemic has dramatically altered the way in which work is conducted, with some suggesting that higher employee age may be a risk factor for diminished wellbeing at work in the face of the pandemic [ 5 , 6 ]. Despite this, research on the experience of healthy aging at work during the pandemic remains scarce thus far [ 7 ].…”
Section: Introductionmentioning
confidence: 99%